2010
DOI: 10.1097/ico.0b013e3181d2de91
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Keratitis Treated With Corneal Crosslinking

Abstract: Our experience based on the above and other cases suggest that CXL could be an effective tool in battling difficult cases of infectious keratitis. This treatment could present many advantages but will need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 34 publications
(43 reference statements)
6
105
0
15
Order By: Relevance
“…Studies show that therapeutic transplants represent 2.6% to 17.9% of total penetrating transplants (17) . There are reports of corneal ulcers treated successfully with corneal collagen crosslinking (CXL) (18)(19)(20)(21)(22)(23)(24)(25) . An experimental study found increased resistance to enzymatic digestion by collagenase, pepsin, and trypsin in corneas subjected to CXL (26) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that therapeutic transplants represent 2.6% to 17.9% of total penetrating transplants (17) . There are reports of corneal ulcers treated successfully with corneal collagen crosslinking (CXL) (18)(19)(20)(21)(22)(23)(24)(25) . An experimental study found increased resistance to enzymatic digestion by collagenase, pepsin, and trypsin in corneas subjected to CXL (26) .…”
mentioning
confidence: 99%
“…Currently, CXL is usually indicated for cases of keratoconus (30) , pellucid marginal degeneration (31) , painful bullous keratopathy (32) , and iatrogenic ectasia after refractive surgery with laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK) (30) . The therapeutic effects of CXL in infectious keratitis are still unclear (18)(19)(20)(21)(22)(23)(24)(25)(26) . This study aimed to evaluate the effect of CXL on infectious keratitis resistant to medical treatment.…”
mentioning
confidence: 99%
“…Pri vseh pa je tudi prišlo do popolne epitalizacije in zaustavitve mehčanja roženice. 43 Mehčanje roženice je resno stanje, ki lahko privede do perforacije roženi-ce in izgube vida. Poleg standardnega zdravljenja je CXL dodatna terapevtska možnost.…”
Section: In Okužbe Roženiceunclassified
“…UV irradiation onto riboflavin saturated cornea generates oxygen and superoxide anion radicals, which induce intra and/or interhelical collagen cross-links and also inactivate microbial pathogens [47]. Several studies demonstrated in vitro antimicrobial activity of corneal collagen cross linking against various pathogens [48][49][50]. Riboflavin/UVA adjuvant to antifungal therapy seems to be a promising technique for management of fungal keratitis.…”
Section: Newer Modality Of Treatmentmentioning
confidence: 99%